Functionalized Fluorescent Silica Nanoparticles for Bioimaging of Cancer Cells - Ruth Prieto-Montero; Alberto Katsumiti; Miren Pilare Cajaraville; Iñigo López-Arbeloa; Virginia Martínez-Martínez (Sensors, 2020)
Functionalized fluorescent silica nanoparticles were designed and synthesized to selectively target cancer cells for bioimaging analysis. The synthesis method and characterization of functionalized fluorescent silica nanoparticles (50–60 nm), as well as internalization and subcellular localization in HeLa cells is reported here. The dye, rhodamine 101 (R101) was physically embedded during the sol–gel synthesis. The dye loading was optimized by varying the synthesis conditions (temperature and dye concentration added to the gel) and by the use of different organotriethoxysilanes as a second silica precursor. Additionally, R101, was also covalently bound to the functionalized external surface of the silica nanoparticles. The quantum yields of the dye-doped silica nanoparticles range from 0.25 to 0.50 and demonstrated an enhanced brightness of 230–260 fold respect to the free dye in solution. The shell of the nanoparticles was further decorated with PEG of 2000 Da and folic acid (FA) to ensure good stability in water and to enhance selectivity to cancer cells, respectively. In vitro assays with HeLa cells showed that fluorescent nanoparticles were internalized by cells accumulating exclusively into lysosomes. Quantitative analysis showed a significantly higher accumulation of FA functionalized fluorescent silica nanoparticles compared to nanoparticles without FA, proving that the former may represent good candidates for targeting cancer cells.